Exploring and Depicting Information Pathologies: A Case Study of Information Technology Anxiety and Information Overload - Vicente, Paulo (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2024)
This study addresses two information pathologies: information technology anxiety (ITA) and information overload (IO). This research aims to determine the level of both ITA and IO amongst the undergraduate students of Information Science of the Faculty of Arts and Humanities of the University of Coimbra, Portugal, and to ascertain how both phenomena correlate with students’ gender, age, number of enrolments in the degree and average frequency of use of the university’s libraries throughout the academic year. Concerning the research methodology, we opted for exploratory and descriptive research with a quantitative approach and adopted the case study and questionnaire survey methods. Both descriptive and inferential statistics were used as methods of data analysis. The findings, concerning 39% of the population under study (N = 88; n = 34), reveal a considerably low prevalence of ITA but a substantial occurrence of IO. Both ITA and IO correlate positively with the female gender. Students aged 19 and 24 years are the least likely to manifest both ITA and IO; in turn, students aged 22 years are the most likely to simultaneously show ITA and IO. Both phenomena tend to increase as students progress through the degree. Last, a higher frequency of use of the university’s libraries is associated with a higher level of ITA and IO. Our findings emphasize the high incidence of IO in university students and the need for increased skills in all dimensions of the human-information-technology relationship/system, particularly in the information filtering and management areas.